2014
DOI: 10.1016/j.poetic.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

An eclectic eclecticism: Methodological and theoretical issues about the quantification of cultural omnivorism

Abstract: International audienceCultural eclecticism has been the focus of most sociological debates pertaining to cultural practices since the publication of Richard Peterson's first articles on the topic. Underlying these debates surrounding results, the prevailing definitions and methods are particularly striking for their… eclecticism. And although it is not explicitly stated, it appears that sociologists disagree over the parameters of inquiry – how the object of study is constructed and all manner of methodologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 25 publications
1
27
0
4
Order By: Relevance
“…However, there are fundamental problems with the concept of the cultural omnivore, in terms of the ways in which taste is measured and the ways in which its implications are interpreted (see e.g. Atkinson ; Holt ; Jarness ; Lahire ; Robette and Roueff ; Savage and Gayo ). We highlight two incisive critiques here.…”
Section: Omnivorousness or Classed Tastes?mentioning
confidence: 99%
“…However, there are fundamental problems with the concept of the cultural omnivore, in terms of the ways in which taste is measured and the ways in which its implications are interpreted (see e.g. Atkinson ; Holt ; Jarness ; Lahire ; Robette and Roueff ; Savage and Gayo ). We highlight two incisive critiques here.…”
Section: Omnivorousness or Classed Tastes?mentioning
confidence: 99%
“…Comme l'ont noté Richard A. Peterson et Roger M. Kern (), Philippe Coulangeon (), Omar Lizardo et Sara Skiles (), Nicolas Robette et Olivier Roueff () ou encore Adrian Leguina (), le modèle de l'omnivorité (Peterson ; Peterson et Kern ; Peterson et Simkus ) actualise et prolonge plus qu'il ne contredit le modèle de l'homologie structurale élaboré par P. Bourdieu. Bien qu'il soit monnaie courante de les opposer (Atkinson ; Bryson ; Veenstra ), ces deux perspectives ne sont pas antithétiques.…”
unclassified
“…There are additional reasons to question the purported ‘openness’ of omnivores and these relate to the category of the ‘omnivore’ itself. Although the notion of a divide between ‘omnivores’ and ‘univores’ is now widespread in cultural sociology, research has also found significant problems with this conceptualization, questioning its validity and usefulness (see, e.g., Atkinson ; Friedman ; Ollivier ; Prieur and Savage ; Rimmer ; Robette and Roueff ; Savage and Gayo ). For instance, Robette and Roeuf have shown that beneath an apparent scientific consensus lies an eclectic array of methodology in the indicators and methods used to operationalize ‘omnivorousness’, leading to disparate results and to authors using the same term while writing about different phenomena.…”
Section: Does Liking Classical Music and Jazz Make You Aesthetically mentioning
confidence: 99%